2019
DOI: 10.1002/ijgo.12871
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for the management of the social and ethical challenges in brain death during pregnancy

Abstract: The aim of the present study is to assess the ethical, legal, and social issues of brain death in pregnancy through a literature review, and, based on the review results, to provide ethical and social guidelines. A search of PubMed using MeSH terms was conducted and yielded 844 results for the period from 1979 to 2017. After articles were screened based on the title and abstract content, 45 were found to refer to the existing ethical, social, and legal implications in cases of brain death during pregnancy, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Costs should not be underestimated; however, they should not be the primary concern and focus. Also, an international registry of brain-dead pregnant patients should be established [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Costs should not be underestimated; however, they should not be the primary concern and focus. Also, an international registry of brain-dead pregnant patients should be established [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…From the legal standpoint, a study by Lewis et al showed that nearly 100% of hospital protocols do not address the identity of the decision maker for the fetus, leaving open the vast possibilities of the father, mother's next of kin, physicians, hospital administration, risk management, ethics committee, legal representative, or even the state [7]. In 2019, a study published by Cartolvni et al proposed guidelines for the management of social and ethical aspects of brain death during pregnancy [7][8][9]. They proposed to adequately determine the mother's brain death state, assess the viability of the fetus, check with the father of the child, next of kin, family, and mother's previously expressed wishes, organize a combined meeting of the interdisciplinary team comprising physicians, caregiving team, hospital ethics committee, and members of the family to discuss fetal prognosis, mother's wishes, and emotional and financial factors, organize adequate support to the father, next of kin, or members of the family, seek to establish a decision within a clinical setting, avoiding the Court if possible, and only appeal to the Court in cases when a decision cannot be made between the members of the family or when it is perceived that their decision is not in the interests of the fetus and is contrary to good obstetric practice.…”
Section: Discussionmentioning
confidence: 99%
“…There are no specific legal regulations associated with somatic support after BD is diagnosed during pregnancy in the Czech Republic, and a wide range of options are present in different countries. The International Federation of Gynecology and Obstetrics has published guidelines for the management of the social and ethical challenges presented by BD during pregnancy [ 8 ]. The guidelines outline 6 key recommendations for the management of brain-dead pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…Medical and legal experts of organized forensics in obstetrics and medical ethics emphasize exaggerated pluralism and liberalism in decisions to end NMICS pregnancies that, in the event of potential complications and adverse outcomes (maternal or child death, permanent disability), have significant legislative and public repercussions, regardless of informed consent coverage, such as the recently reported case of maternal death from intracranial hemorrhage as a complication of spinal anesthesia in ECS indicated due to tocophobia [15]. Patient autonomy implies that the provision of a health service that has no justification in the patient's valid consent has the character of injury to the patient's body and personality (physical and mental integrity), which is interpreted, in civil law, as a violation of personality rights and non-pecuniary damage, while medical and legal authorities interpret that the injury to the body is itself an indication of unlawfulness, including medical treatment performed on the body of a patient [9,[23][24][25].…”
Section: Discussionmentioning
confidence: 99%